Present Situation and Development Trend of Oil and Gas Well Perforation Technology (International Journal of Scientific Research and Management (IJSRM), 2025)
Perforation technology is a key process in oil and gas development. With the continuous improvement of the complexity of oil and gas development objects and operation requirements, perforation technology has experienced an evolution process from simply opening oil and gas channels to protecting oil and gas reservoirs, improving completion effects, and then combining with production stimulation measures to further liberate oil and gas reservoirs. During this period, a series of advanced technologies and supporting processes such as negative pressure perforation, composite perforation, combined perforation, ultra-high temperature and ultra-high pressure perforation, fixed surface/orientation/fixed azimuth/fixed angle perforation, and cluster perforation have been developed, which have significantly improved the completion effect, increased production and transformation effect, and protected oil and gas reservoirs and improved operation efficiency. However, there is still a certain gap between perforation technology in our country and foreign countries. By combing the current situation of perforation technology, analyzing the technical gap between China and foreign countries, and combining the actual situation and characteristics of China’s oil and gas development, this paper puts forward targeted perforation technology development suggestions, aiming to promote the progress of perforation technology, make it better serve oil and gas development, and provide technical support for the high-quality development of our country’s oil and gas industry.